2019
DOI: 10.1016/j.ijscr.2019.06.060
|View full text |Cite
|
Sign up to set email alerts
|

Mixed neuroendocrine and squamous cell carcinoma of the colon: A case report and literature review

Abstract: Highlights We present the first case of primary colon mixed NEC and SCC which presented with abdominal pain. The tumor was resected, and patient was set to start chemotherapy treatment. There is not sufficient literature addressing ideal adjuvant therapy after resection of mixed NEC and SCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Neuroendocrine differentiation was confirmed by strong immunohistochemical positivity for synaptophysin, which has been approved as the best single marker for neuroendocrine tumours [27]. In accordance with one previous study, we found remarkably strong nuclear expression of CDX2 and β-catenin in over 90% of tumour cells of both carcinoma cases as well as in both components (neuroendocrine and squamous) of the tumours [7]. The high Frequencies of genetic alterations (in percent) of colorectal adenocarcinomas (AC), MiNENs, neuroendocrine carcinomas (NEC) in three studies (The Cancer Genome Atlas Program 2012 (TCGA, [16]), Jesinghaus et al [48] and Woischke et al [47]) in comparison with the genetic alterations of the two cases of mixed large cell neuroendocrine carcinoma and squamous cell carcinoma.…”
Section: Woischke Et Alsupporting
confidence: 91%
See 2 more Smart Citations
“…Neuroendocrine differentiation was confirmed by strong immunohistochemical positivity for synaptophysin, which has been approved as the best single marker for neuroendocrine tumours [27]. In accordance with one previous study, we found remarkably strong nuclear expression of CDX2 and β-catenin in over 90% of tumour cells of both carcinoma cases as well as in both components (neuroendocrine and squamous) of the tumours [7]. The high Frequencies of genetic alterations (in percent) of colorectal adenocarcinomas (AC), MiNENs, neuroendocrine carcinomas (NEC) in three studies (The Cancer Genome Atlas Program 2012 (TCGA, [16]), Jesinghaus et al [48] and Woischke et al [47]) in comparison with the genetic alterations of the two cases of mixed large cell neuroendocrine carcinoma and squamous cell carcinoma.…”
Section: Woischke Et Alsupporting
confidence: 91%
“…In accordance with the new World Health Organization Classification from 2019, mixed large cell neuroendocrine carcinoma and squamous cell carcinoma in the colorectum is subsumed under the category of MiNENs, formerly named MANECs, in which each component accounts for ≥30% of the neoplasm [24]. Although three case reports of mixed neuroendocrine carcinoma and squamous cell carcinoma of the colorectum in literature do exist [5][6][7], only one of Values indicate the existence (1) or non-existence (0) of significant co-occurrence, or significant mutual exclusivity between the listed mutated genes in three different data sets according to The Cancer Genome Atlas Program 2012 (TCGA, [16]), TCGA Pan Cancer Atlas Study [17] and Memorial Sloan Kettering Cancer Center Study (MSKCC, [18]). No significant finding is shown in red, significant correlation in one data set is marked in orange and significant findings in two or more data sets are highlighted in green.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, there are a few reports of mixed neuroendocrine non-neuroendocrine neoplasms (MiNEN) and NEC collision with SCC in the esophagus (Mendoza-Moreno et al, 2018 ; Choe et al, 2020 ); to the best of our knowledge, the current case is the first to be reported wherein a metachronous development of NEC and SCC is seen in the EGJ. In previous reports of MiNEN and collision carcinoma (Elkbuli et al, 2019 ; Kaneko et al, 2019 ; Choe et al, 2020 ), SCC was found on the surface of the mucosa, while NEC was found at a deeper level in the pathological sample. In the present case, NEC was found on the surface of the mucosa without any SCC components or adenocarcinoma, suggesting that NEC primarily occurred in the EGJ.…”
Section: Discussionmentioning
confidence: 84%
“…Alternative thresholds of 10% or 20% as discriminatory cut of criterion need to be explored as even the presence of small focus of NEC can be associated with aggressive behavior and metastases[ 18 , 20 ]. Most neuroendocrine neoplasms (NEN) in high grade cancers are PDNEC either large (82.2%) or small cell (17.8%) admixed with a non-neuroendocrine component-epithelial tumor usually adenocarcinoma NOS or mucinous/signet ring cell adenocarcinoma (92.2%), though squamous cell carcinoma (2.5%) and other variants such as adenosquamous (< 1%), AFP negative hepatoid carcinoma (< 1%)have also been reported[ 18 , 20 , 84 , 86 , 90 , 91 , 94 , 102 , 103 ]. Histologically, the poorly differentiated neuroendocrine component resembles small or large cell NEC tumors.…”
Section: Discussionmentioning
confidence: 99%